Statistics with confidence - Smithson, Michael (Sage foundations of psychology series., 2000)
In a new approach, Michael Smithson corrects some widely acknowledged problems associated with traditional approaches to psychometrics in the psychology setting. The author assumes the reader has a basic understanding of statistics.